The Effect of Registration Taxes on New Car Sales and Emissions: Evidence from Switzerland - Anna Alberini; Markus Bareit (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
In Switzerland, the annual circulation taxes on road vehicles are set by and paid to the cantons (not to the federal government). We exploit the 26 different circulation tax rules and their variation over time, which we interpret as a natural experiment, to see if linking them to a vehicle's CO2 emissions rate has helped shift new car sales towards cleaner, lower-emitting vehicles. We find that even when the penalty associated with a highly polluting vehicle is high, the effect is relatively small. For example, in canton Zurich, imposing a 50% “malus” on the annual registration fee for cars that emit 200 or more grams of CO2 per kilometer reduces the average CO2 emissions rate from new cars by only 0.46 gram per kilometer, bringing it to 158.11 grams per kilometer in 2011. A similar effect would be attained with a modest increase in fuel taxes.
Keywords: L62; Q4; Q5; 330; vehicle demand estimation; fuel economy; fuel taxes; vehicle taxes; carbon dioxide emissions rates; Kraftfahrzeugsteuer; Mineralölsteuer; Wirkungsanalyse; Kraftfahrzeug; Absatz; Treibhausgas-Emissionen; Schweiz